Modulation of Regulatory T Cell Activity by TNF Receptor Type II-Targeting Pharmacological Agents - Zou, Huimin; Li, Ruixin; Hu, Hao; Hu, Yuanjia; Chen, Xin (Frontiers in Immunology, 2018)
There is now compelling evidence that tumor necrosis factor (TNF)–TNF receptor type II (TNFR2) interaction plays a decisive role in the activation, expansion, and phenotypical stability of suppressive CD4+Foxp3+ regulatory T cells (Tregs). In an effort to translate this basic research finding into a therapeutic benefit, a number of agonistic or antagonistic TNFR2-targeting biological agents with the capacity to activate or inhibit Treg activity have been developed and studied. Recent studies also show that thalidomide analogs, cyclophosphamide, and other small molecules are able to act on TNFR2, resulting in the elimination of TNFR2-expressing Tregs. In contrast, pharmacological agents, such as vitamin D3 and adalimumab, were reported to induce the expansion of Tregs by promoting the interaction of transmembrane TNF (tmTNF) with TNFR2. These studies clearly show that TNFR2-targeting pharmacological agents represent an effective approach to modulating the function of Tregs and thus may be useful in the treatment of major human diseases such as autoimmune disorders, graft-versus-host disease (GVHD), and cancer. In this review, we will summarize and discuss the latest progress in the study of TNFR2-targeting pharmacological agents and their therapeutic potential based on upregulation or downregulation of Treg activity.